Answer:
The output is given as [tex]y(n)=x[n]-2x[n-1]+3x[n-2][/tex]
Step-by-step explanation:
As the output is given as y(n) and the input is given as x(n) thus the
equation of the output is given as
[tex]y(n)=h(n)*x(n)[/tex]
Here the impulse response h(n) is given as
[tex]h(n)=\delta[n]-2\delta[n-1]+3\delta[n-2][/tex]
So the output is given as
[tex]y(n)=h(n)*x(n)\\y(n)=(\delta[n]-2\delta[n-1]+3\delta[n-2])*x(n)[/tex]
By distributive property,[tex](ax1[n] + bx2[n]) * h[n] = ax1[n] * h[n] + bx2[n] * h[n][/tex]
[tex]y(n)=h(n)*x(n)\\y(n)=\delta[n]*x(n)-2\delta[n-1]*x(n)+3\delta[n-2]*x(n)[/tex]
Now by the convolution properties with delta [tex]\delta[n- k] *x[n] = x[n-k][/tex]
so
[tex]y(n)=\delta[n]*x(n)-2\delta[n-1]*x(n)+3\delta[n-2]*x(n)\\y(n)=\delta[n-0]*x(n)-2\delta[n-1]*x(n)+3\delta[n-2]*x(n)\\y(n)=x[n]-2x[n-1]+3x[n-2][/tex]
So the output is given as [tex]y(n)=x[n]-2x[n-1]+3x[n-2][/tex]